Bronchiectasis among Australian Aboriginal and non-Aboriginal patients in the regional and remote population of the Northern Territory of Australia - Sumit Mehra; Anne Chang; Chor Lam; Stuart Campbell; Joy Mingi; Izaak Thomas; Suzanne Harwood; Graeme Maguire; Subash Heraganahally (James Cook University, 2021)
Introduction: Chronic respiratory disorders are highly prevalent among Australian Aboriginal people living in the Top End Health Service region in the Northern Territory, Australia. Bronchiectasis is a heterogenous disease that features among these chronic respiratory conditions in this population. However, there are sparse comparative data between Aboriginal and non-Aboriginal patients with bronchiectasis from this region. Methods: In this retrospective study, demographics, clinical characteristics and relevant laboratory parameters were compared among adult Aboriginal and non-Aboriginal patients diagnosed with bronchiectasis between 2012 and 2017. Results: A total of 388 adults had radiology-confirmed bronchiectasis and 258 (66%) were Aboriginal. Compared to non-Aboriginal patients, Aboriginal patients were significantly younger (mean age 54 v 67 years), the majority lived in rural and remote communities (80% v 9 %), had higher rates of self-reported smoking (52% v 19%), alcohol consumption (29% v 12%) and co-occurrence of chronic obstructive pulmonary disease (65% v 38%) and other chronic co-morbidities. Sputum microbiology was also different between the groups with Haemophilus influenzae, Streptococcus pneumoniae and Moraxella catarrhalis being more common in Aboriginal patients, while Pseudomonas aeruginosa, Aspergillus species and non-tuberculous mycobacteria were higher in non-Aboriginal patients. Further, Aboriginal patients had poorer lung function compared to non-Aboriginal patients (forced expiratory volume after 1 second predicted 33% v 53%, forced vital capacity predicted 49% v 60% respectively), higher exacerbation rates (29% v 18%) and poorer overall outcomes (age at death 60 v 76 years). Conclusion: Within a single health service, Aboriginal patients with bronchiectasis have significantly poorer outcomes with differing manifestations and higher comorbidities than non-Aboriginal patients. This warrants further studies to identify feasible interventions to reduce this inequity.